An African feminist analysis on the experiences of black African immigrant men in Cape Town, South Africa - Dywati, Zandile Joy (African Studies, 2025)
Practices of masculinities amongst migrant men are greatly dependent on the resources that these men can mobilize within a new national and cultural context. This research study provides a gendered perspective on migration studies that postulate the embedded impact of gender ideologies within migrant households, and communities, impacting men as 'gendered' and ‘sexual identities'. This research study argues against the homogenizing and essentialist notions of researching immigrants as ungendered subjects. It positions the importance of utilizing Decolonial African Feminist theorizations in migration studies towards rendering visible men and masculinities in research on African mobilities. This research study focuses on deconstructing taken-for-granted assumptions of what it means to be a black African, and how these are embodied within migratory masculine identities in South Africa. It provides the life stories of six African men, aiming to explore African masculinities within transnational migration studies and provides a nuanced understanding of how masculinities are made, remade, and maintained across geographies, and socio-economic and -cultural configurations of racialized masculine subjectivities. The findings and discussions of this research study reveal the gendered narratives of migration especially men's marginalization, vulnerabilities, performances of fathering, family ties, and religiosity in a more nuanced approach that embraces the critical insights into the inequalities that these men experience. Some of the key findings of this research study surface the negotiation of their masculine subjectivities as these men experience various forms of systematic and institutionalized violences and victimization. Moreover, the findings of this research study unpack the pathways of moving away and towards hegemonic masculine ideals as a form of repairing their manhood through embodying affective forms of masculinities as they navigate masculinities fathering, and fatherhood. Lastly, this study's findings unpack how immigrant men embody heteropatriarchal religious and cultural masculine ideologies in attempts to repair their lost masculine status.